Interfacial mechanics investigation of transmission components under non-Newtonian lubrication conditions - Bai, Xueyu (Nanyang Technological University, 2023)
Elastohydrodynamic lubrication (EHL) is one of the most common lubrication modes in a non-conformal contact interface system, which consists of two elastic solid-body surfaces in contact and relative motion with fluid in between. Typically, transmission components undergoing thermal EHL often operate under non-Newtonian and starved lubrication. This severe condition strongly alters the interfacial mechanics and deserves more investigation. Reliable and stable numerical models of EHL are beneficial for risk evaluation at workplaces and structural optimization. However, the integration of multiphysics, such as mechano-, hydro-, dyno- and thermo-fields, is a great challenge in modelling EHL problems. Hence, this PhD research focuses on developing such an integrated numerical model to investigate the interfacial mechanics of transmission components under non-Newtonian starved thermal EHL conditions. Thus far, the following studies have been conducted. First, both the finite difference (FD) and finite element (FE) numerical models of the transmission components under thermal EHL have been developed considering the non-Newtonian behaviours and lubrication starvation. The former has advantages in modelling heterogeneous materials and high simulation efficiency, while the latter is readily implemented with commercial software and thus can be widely applied in industries. The Elrod algorithm is adopted to determine the lubrication starvation based on the solutions of pressure and film thickness. The lubricant velocity and shear rate are derived by using the separation flow method to account for the non-Newtonian rheological properties of the lubricants. Solutions of three typical non-Newtonian lubricants are discussed to reveal the rheological effects on the flow-field and lubrication properties under different operating conditions. The results reveal that non-Newtonian rheological behaviours substantially influence lubricant friction and temperature. The solutions of lubrication of machined rough surfaces and heterogeneous materials are also presented to demonstrate the generality of the developed models. Second, the FD-based model of heterogeneous materials is extended to an EHL system in impact motion, which exists universally in lubricated machinery. A rigid ball bounces on an oil-covered plane surface of an elastic half-space with inhomogeneous inclusions. The inhomogeneous inclusion within the materials is homogenized with unknown eigenstrains according to the equivalent inclusion method. The lubricant pressure, film thickness, fractional film content, temperature, and subsurface elastic fields are presented to illustrate the essential features in the space domain of starved thermal EHL subjected to impact. The dynamic responses of the EHL system are revealed by demonstrating the variations of the central pressure, central film thickness, minimum film thickness, dimensionless central temperature, and maximum von Mises stress with time. The impact–rebound process and the microscopic response of the subsurface inhomogeneous inclusions are investigated in the cases subjected to constant impact mass, momentum, and energy. The drop height determines the dynamic responses during the early approaching process. Meanwhile, the impact energy is the decisive factor for the peak stress, maximum hydrodynamic force, and restitution coefficient. Finally, the FD-based EHL model of heterogeneous materials in impact motion is further extended to plasto-elastohydrodynamic lubrication (PEHL). Accumulated plastic strain is obtained by an iterative method involving a plasticity loop based on the stress state analysis. Surface displacements induced by eigenstrains and plastic strains are introduced into the gap between the contacting bodies to update the lubrication film thickness until convergence is achieved. The dynamic responses are discussed, including the pressure, film thickness, starvation parameter, residual deformation, temperature, and subsurface elastoplastic fields during the impact–rebound process. After the model validation against reference data, the effects of material inhomogeneity, plasticity, and strain hardening on the lubrication response are investigated to provide guidance for material reliability analysis. This PhD research contributes to the modelling of EHL problems and provides insights into the interfacial mechanisms of transmission components under severe lubrication conditions. The scientific understanding extracted from the model is constructive and profitable for engineering industries from the aspect of machine performance, efficiency, durability, and reliability.